2007
DOI: 10.1016/j.biopha.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lycorine on SCID mice model with human APL cells

Abstract: In our previous study, lycorine, a natural alkaloid extracted from Amaryllidaceae, exhibited anti-leukemia effects in vitro. To determine whether lycorine has an anti-tumor effect in vivo, a series of experiments were carried out in this study. HL-60 cells (5 x 10(6)) were inoculated i.v. into severe combined immuno-deficiency (SCID) mice after these mice had been irradiated (total body receiving 200cGy chi irradiation). Treatment was given once a day from day 2 to 6, and from day 14 to 18. Lycorine (5 or 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 20 publications
(24 reference statements)
3
39
0
2
Order By: Relevance
“…The antitumor activity of pancratistatin was found to be more potent than sodium pancratistatin 3,4-ocyclic phosphate, reported by Shnyder and colleagues (34) to have antitumor activity at 100 mg/kg. Other Amaryllidaceae alkaloids, including narciclasine and lycorine, have antitumor activity at doses that complement our findings (35,36).…”
Section: Discussionsupporting
confidence: 84%
“…The antitumor activity of pancratistatin was found to be more potent than sodium pancratistatin 3,4-ocyclic phosphate, reported by Shnyder and colleagues (34) to have antitumor activity at 100 mg/kg. Other Amaryllidaceae alkaloids, including narciclasine and lycorine, have antitumor activity at doses that complement our findings (35,36).…”
Section: Discussionsupporting
confidence: 84%
“…Previously, this compound has been shown to possess various pharmacological effects, including significantly higher antiproliferative activities in tumor cell lines compared to normal cells and in vivo activity against the B16F10 melanoma model [46,47]. Previous studies by our group demonstrated that lycorine can inhibit proliferation and induce apoptosis in leukemia cell lines [48][49][50], and lycorine treatment can extend the survival time of human acute promyelocytic leukemia (APL) cells in a SCID mouse xenograft model [51]. The present study was conducted to study the effect and mechanism of lycorine against multiple myeloma.…”
Section: Introductionmentioning
confidence: 93%
“…The in vitro mode of action in a HL-60 leukemia cell line model is associated with suppressing tumor cell growth and reducing cell survival via cell cycle arrest and induction of apoptosis (Liu et al, 2004). Further investigation showed that it is able to decrease tumor cell growth and increase survival rates with no observable adverse effects in treated animals (Liu et al, 2007), thus being a good candidate for a therapeutic agent against leukaemia (Liu et al, 2009).…”
Section: Lycorine-typementioning
confidence: 99%